Read at Home : Guidance Note on the Production of Reading Materials - World Bank (Washington, DC, 2022)
Access to books (textbooks, teacher’s guides, and materials for reading practice) is key to addressing learning poverty. Children need to be exposed to sufficient and appropriate text, and they need to be afforded the time and opportunity to practice reading in school and at home. Appropriate design of reading books will facilitate learning, support instruction, and promote independent learning. This guidance note focuses on straightforward, standard approaches that World Bank teams and clients can use to increase the usefulness and durability and decrease the costs of books in education programs. The first section describes appropriate font types and sizes based on script and grade level, as well as best practices for letter and word spacing. The physical characteristics of books determine printing costs and durability to a large degree, and so the second section discusses these, with a focus on paper and binding. Printing methods and printer selection are critical for book quality and on-time delivery and so the third section covers printing methods and printer selection. Finishing is the last step in book production and is covered in fourth section and packaging is covered in the fifth section. The note ends with a short list of key recommendations.